Financial Development and Economic Growth: Empirical Evidence from a Panel of MENA Countries - Heap, Steffan (2022)
This paper aims to explore the long-standing debate between financial development and economic growth. This is done with the focus of 18 Middle East and North African countries between 2000 and 2021 by obtaining data from the World Bank, World Development Indicators database. The paper seeks to establish the formal statistical links between financial development and economic growth in the context of interactions with levels of domestic credit provided to the private sector, domestic credit provided by the financial sector, and liquid liabilities whilst controlling for trade openness and inflation. The Driscoll-Kraay robust standard errors panel regression model is used to obtain estimations, and the findings are checked for robustness by using GLM, FGLS and system-GMM estimators. Our results find that each of the estimators unanimously finds a positive association between finance and growth for 2 out of 3 of the financial development indicators. The findings suggest that decision-makers in the MENA regions who wish to expand economic growth should pay special attention to the role of the banking sector whilst considering the significant effects that trade openness and inflation also have.